Contracting a Radical Democracy in the Balkans - The Return of the People as a Possibility for a Leftist Inauguration of Politics - Sadiku, Artan (Identities: Journal for Politics, Gender and Culture, 2015)
My aim is to strengthen the argument against the dereliction of the notion of democracy – as it has resulted in the Balkans and elsewhere and to provide a thesis that a radical political change in the Balkans requires the occurrence of a political event by which a new social contract can establish itself as a genuine expression of the will of the people, or more precisely a new mode of state as a result of a new balance of class antagonisms. Reaffirming the notion of the people against its political correlative – the citizen, I aim to prove that the ‘return of the people’ – as concept is crucial for the radicalization of the concept of democracy which enables the leftist politics to be inaugurated into the political proper. Author(s): Artan Sadiku Title (English): Contracting a Radical Democracy in the Balkans - The Return of the People as a Possibility for a Leftist Inauguration of Politics Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 67-88 Page Count: 13 Citation (English): Artan Sadiku, “Contracting a Radical Democracy in the Balkans - The Return of the People as a Possibility for a Leftist Inauguration of Politics,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 67-88.